Surface reflectance for illuminance level control in daylit historical museum gallery under tropical sky conditions - Ahmad, Noraini; Sheikh Ahmad, Sabarinah; Talib, Anuar (Trans Tech Publications, Switzerland, 2013)
Malaysia has tropical sky conditions, receiving plenty of natural light throughout the year. Natural light fluctuates greatly and it can be rather tricky to provide good distribution of daylight throughout an interior space and this prompts the need for strategic daylight control programme in a historic museum gallery. Surface reflectance is a significant design consideration, particularly with regards to how light is distributed throughout an interior space. Research on how the internal surfaces reflectances are controlled for long-term preservation of museum exhibits is still lacking for tropical skies conditions. The study aims to assess the internal surface reflectance contribution at a west facing daylit historical museum gallery through in-situ measurements and simulation model assessment. The results obtained in these experiments are visually compared with the existing surface reflectance values through simulation modelling. The results show new knowledge on light damage issues. The results also highlight daylighting distributions control and light exposure limits through realistic predictions’ images and reflectance’s alterations. The study confirms that surface reflectances can be a control mechanism for preventive conservation in the historical museum gallery.